Use of garlic in postpartum diet and practices in Jaffna district - Menaka, S. (University of Sri Jayewardenepura, Sri Lanka, 2023)
Childbirth is a time of transition and social celebration in many societies. Garlic (Allium sativum) plays an important role in recovery during the postpartum period in diet and bathing practices. The objectives of the study were to find the application and uses of garlic in food and bath practices in postpartum recovery in Jaffna district. Twenty-five mothers who gave birth within two years and twenty-five elder women who look after the mothers after confinement were interviewed regarding the use of garlic in postpartum culinary and bath practices. Pregnancy is seen as a hot state. With parturition, heat is lost and the woman comes into a state of excess cold. During the sensible period, the mothers are given easily digestible foods to promote healing, boost immunity and improve milk supply. A mix is prepared using garlic, cumin, ginger and turmeric, made into small balls and given to mothers to eat with palm sugar before breakfast and dinner. Garlic, pepper, fennel, turmeric and coriander are ground on a grinding stone and used to make curry. Garlic in the mix is believed to heal the wound and improve milk production. Roasted garlic after head bath helps the mothers to restore the equilibrium. ‘Sambrani’ (benzoin resin) smoke with outer garlic peel is applied to hair, which will reduce the cold. Warmed gingelly oil added with outer garlic peel is used to give body and head massage to the newborn. There is a continuum between traditional and modern postpartum care in households. However, garlic plays a major role in healing, boosting immunity, milk production and reducing cold in postpartum recovery.
Keywords: Garlic; Postpartum; Immunity; Healing; Confinement